Molecular mechanistic insight into the anti-hyperuricemic effect of Eucommia ulmoides in mice and rats - Cong Fang (Taylor & Francis Group, 2019)
Context: Eucommia ulmoides Oliver (Eucommiaceae) has various medicinal properties. Our previous studies revealed that Eucommia ulmoides has a protective effect on hyperuricaemia. Objective: This study investigates the effect of Eucommia ulmoides cortex ethanol extract (EU) on hyperuricaemia and explores the underlying mechanism in Kunming mice and Sprague–Dawley rats. Material and methods: Sixty mice and sixty rats were divided into normal control, hyperuricaemia, allopurinol (10 mg/kg) and three EU groups. The EU groups received intragastric EU at 80, 160, 320 mg/kg in mice and 100, 200, 400 mg/kg in rats for 7 days. Serum uric acid (SUA) was measured using a kit. mRNA and proteins were quantified by RT-qPCR and immunohistochemical assays (IHC), respectively. Results: The Maximal Tolerable Dose (MTD) of EU administered intragastrically was 18 g/kg in mice. The intermediate (160 mg/kg) and high (320 mg/kg) EU treatment significantly reduced (p < 0.05) SUA levels to 130.16 μmol/L and 109.29 μmol/L, respectively, and markedly elevated the mRNA expression of organic anion transporters 1 (OAT1) and organic anion transporters 3 (OAT3), while significantly deceasing the mRNA levels of glucose transporter 9 (GLUT9) and uric acid transporter 1 (URAT1) in the mouse kidney (p < 0.05). In hyperuricemic rats, high EU (400 mg/kg) significantly reduced SUA levels to 253.85 μmol/L, and increased OAT1 and OAT3 levels, but decreased URAT1 and GLUT9, compared to the hyperuricaemia group (p < 0.05). Discussion and conclusions: This study demonstrated the potential hyperuricaemia ameliorating effect of EU. Specific active ingredients in EU should be evaluated. These results are valuable for the development of antihyperuritic agents from EU.